A STUDY TO ASSESS THE EFFECTIVENESS OF BREATHING STRATEGIES ON RESPIRATORY PARAMETERS AMONG ICU PATIENTS IN SELECTED HOSPITAL - Dr Sushma Pandey, Archana Singh (Obstetrics and Gynaecology Forum, 2024)
Abstract Breathing is the most vital functioning for maintenance of life. Respiratory function of the lung is critical and of immediate importance for the survival of organisms, and molecular oxygen is vital for energy that is essential for life. The physiological model of the lung consists of conducting airways to transport the gas in and out of the lungs and the alveolar membranes where gas exchange occurs by diffusion from the alveoli to capillaries within the lungs, oxygen diffuses freely through the cells that from the alveolar septa to the pulmonary capillaries for eventual distribution by the systemic blood. The main purpose of breathing strategies is to assist the patients in removal of secretions, correct abnormal breathing patterns and decreases the work of breathing, aid in bronchial hygiene – prevent accumulation of pulmonary secretions, mobilization of these secretions and improves cough mechanism.